2000
DOI: 10.1177/039139880002301209
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Apheresis in Children: Experience in a Pediatric Dialysis Center

Abstract: The use of apheretic procedures in pediatric patients has always been restricted by technical difficulties and the low incidence of diseases requiring this kind of treatment. The aim of the present study was to describe the solutions adopted to solve technical difficulties related to priming, vascular access and monitoring and then to evaluate clinical results. Between 1982 and 2000, 51 consecutive children (28 male, 23 female) with a mean age of 4.9 ± 4.8 years (3 months – 14.8 years) and a mean weight of 19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Comparing our study with De Palo et al's [4] report, we found that the blood fl ow and turnover rates resembled our own fi ndings. Our maximum blood fl ow rate (109 8 63 ml/min) slightly exceeded their recommendation of 20-100 ml/min.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Comparing our study with De Palo et al's [4] report, we found that the blood fl ow and turnover rates resembled our own fi ndings. Our maximum blood fl ow rate (109 8 63 ml/min) slightly exceeded their recommendation of 20-100 ml/min.…”
Section: Discussionsupporting
confidence: 90%
“…Our maximum turnover rate (0.72 8 0.32 l/h) approximated their recommendation of 0.3-1.2 l/h. The major indication for PE was diarrhea-associated HUS in De Palo et al's [4] series. In our series, the most common indication for PE was medication-resistant FSGS.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations